Microemulsion – A Potential Carrier for Improved Bioavailability: Microemulsion – A Potential Carrier for Improved Bioavailability - Goswami, Priyanka (International Journal of Pharmaceutical & Biological Archive, 2019)
Microemulsion (ME) are one of the potential and emerging drug carrier systems that help to improve the drug release and enhance the bioavailability of poorly aqueous soluble drugs. These are considered as thermodynamically stable system which mainly consists of three to five components such as aqueous phase, an oil phase, surfactant, cosurfactant, and in some cases electrolyte. Microemulsion became more popular as a drug delivery system, due to some of its unique features such as its capacity to increase the bioavailability, long shelf life and ease of preparation, and huge scope of application. The delivery system is widely used in different filed such as pharmaceutical, food industries, and cosmetics industries. As per literature, around 40% of the newly arrived drug molecules are poorly water-soluble in nature and results in poor bioavailability. Therefore, ME drug delivery system may play a key role to overcome the mentioned issue. Hence, the review has been written with an aim to address the capacity of ME drug delivery system to overcome the solubility issue of poor water-insoluble drugs and to provide adequate information’s about its possible application.